Increasing Radiation Dose to the Thoracic Marrow Is Associated With Acute Hematologic Toxicities in Patients Receiving Chemoradiation for Esophageal Cancer - Fabian, Denise; Ayan, Ahmet; DiCostanzo, Dominic; Barney, Christian L.; Aljabban, Jihad; Diaz, Dayssy A.; Miller, Eric D.; Wuthrick, Evan; Williams, Terence M.; Bazan, Jose G. (Frontiers in Oncology, 2019)
Purpose: To test the hypothesis that increasing radiation dose to the thoracic marrow (TM) contributes to the development of hematologic toxicities (HT) in esophageal cancer (EC) patients receiving chemoradiation therapy (CRT). Methods: We identified EC cases treated with curative intent CRT at our institution from 2007-2016. The TM was contoured as the union of the vertebral bodies (VB) from T1-L1, the ribs from T1-L1, and the sternum. The TM-mean dose and the TM volume receiving at least 5-50 Gy (V5-V50) were collected. Grade≥3 HT (HT3+) was the primary endpoint. Normal tissue complication probability (NTCP) was evaluated using the Lyman-Kutcher-Burman (LKB) model. Logistic regression was used to test associations between HT3+ and dosimetric parameters. Odds ratios (OR) and 95% confidence intervals (CI) are reported with p<0.05 considered significant. Receiver operating characteristics analysis was used to determine optimal cut points. Results: We identified 137 EC cases, and most received concurrent carboplatin/paclitaxel (N=83). Median radiation dose was 50.4 Gy (IQR=50.4-50.4 Gy). The rate of HT3+ was 39.4%. Optimization of the LKB model yielded the results n=0.70, m=0.67, and TD50=20.1 Gy. The TM-V30 was most strongly associated with HT3+ and on multivariate analysis, patients with TM-V30≥14% had a 5.7-fold (95% CI 2.42-14.54, p<0.001) increased odds of HT3+ in the entire cohort and a 4-fold (95% CI 1.54-11.11, p=0.006) increased odds of HT3+ in the carboplatin/paclitaxel cohort compared to patients with TM-V30<14%. Radiation dose to the VB and rib sub-sites of the TM were also associated with HT3+, particularly VB-V40. Conclusion: We found that increasing TM radiation dose was associated with HT3+ in EC patients treated with CRT. Radiation dose to the VB and rib sub-sites were also associated with HT3+. These findings suggest that limiting radiation dose to the TM (or its sub-sites) may be sufficient to decrease HT3+, but further prospective evaluation of these results is needed.